Technical Trends of Cottage Ceramic Industries in Southwestern Nigeria - Segun Oladapo Abiodun (Journal of Visual Art and Design, 2018)
The establishment of modern cottage ceramic industry in Nigeria was the result of changes in taste and demand related to ceramic products influenced by contact with the West. Strategies adopted in transforming Nigerian indigenous pottery to modern ceramics with a mass-production orientation have been featured in several academic publications. However, there has been inadequate academic attention for technical trends in the ceramic industries in Nigeria. This study examined technical trends in cottage ceramic industries in Southwestern Nigeria. Its objectives were to observe styles, techniques and factors that affect the development of these industries. The study adopted studio-practice participant observation and descriptive methodologies. It was observed that most of the cottage ceramic industries in Southwestern Nigeria are using appropriate and intermediate technologies by sourcing their materials, tools and equipment locally. Throwing is the major technique of production used, while painted decorative wares are the dominant products as the cost of producing glaze wares is high. The inability to produce cheaper ceramic wares compared to imported wares leads to low patronage of their products. Improving technical capacities of these industries through various research findings and technological breakthroughs will go a long way to increase the productivity and sustainability of these industries.